Pengaruh Promosi, Kepercayaan, Dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan Produk Iphone di kota Batam - Liau Shelly; Nora Pitri Nainggolan (SCIENTIA JOURNAL, 2025)
Customer loyalty is a crucial factor in maintaining business sustainability, especially in the highly competitive technology industry, such as iPhone products. This study aims to analyze the influence of promotion, trust, and customer satisfaction on customer loyalty to iPhone products in Batam City. The research employs a quantitative approach using a survey method, where data is collected through questionnaires distributed to iPhone users in Batam City. Multiple linear regression analysis is used to examine the relationship between the independent variables (promotion, trust, and customer satisfaction) and the dependent variable (customer loyalty). The results indicate that promotion has a positive but insignificant effect on customer loyalty, while trust and customer satisfaction have a positive and significant impact on customer loyalty. These findings suggest that the higher the level of trust and customer satisfaction, the greater the likelihood that customers will remain loyal to iPhone products. This study provides implications for companies in designing more effective marketing strategies by enhancing trust and customer satisfaction to maintain customer loyalty.